Motivational style of the professor and academic satisfaction in engineering students - Tacca Huamán, Daniel Rubén (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The objective of the research was to know the relationship between the professor’s motivational style and academic satisfaction in students from two private universities in Lima, Peru, in the context of virtual education. The research was quantitative, correlational, non-experimental and involved 776 students from the engineering faculty. A positive and significant relationship was observed between the style that promotes autonomy and academic satisfaction (.538), while the control style obtained a negative relationship with satisfaction (-.092). Industrial engineering students express more satisfaction with the style that promotes autonomy.